Investigating the factors of SMEs' business resilience in the post-pandemic crisis of COVID-19 with technology adoption as a quasi-moderator: a multigroup analysis of Indonesian and Malaysian SMEs - Elissa Dwi Lestari; Nadiah Abd Hamid; Roszilah Shamsuddin; Florentina Kurniasari; Zalilawati Yaacob (Cogent Business & Management, 2024)
In spite of the devastating effects of COVID-19 on businesses, many SMEs have demonstrated resilience and continued on with their operations. This study investigates the determinants of SMEs' business resilience in Malaysia and Indonesia, with a focus on the moderating factor of technology adoption. The Resource-Based View (RBV) Theory, the Dynamic Capability View Theory (DCV), and the Technology-Organization-Environment (TOE) Framework were combined to analyze a set of business resilience-impacting factors in each country. Online surveys with respondents were used to gather data. Partial least squares-based structural equation modeling was used to examine a total of 539 respondents, of whom 335 were from Indonesia and 204 were from Malaysia. The results showed that government support, technological use, and compliance costs have a significant direct impact on the business resilience of SMEs in both countries. Notably, it was discovered that there were insignificant effects from financial resources and financial literacy. The association between financial resources and business resilience in Indonesia and the relationship between government support and business resilience in Malaysia are both negatively moderated by technology adoption. The findings of this study contributed to a multigroup analysis between neighboring countries, offering valuable insights on the factors influencing SMEs' business resilience to withstand the COVID-19 crisis and their subsequent recovery. It helps explain how SMEs cope with the epidemic, use government support, and use technology to adapt to the changing business climate. These findings enabled SMEs and governments to use preparation and resilience methods to anticipate future difficulties.
Keywords: L00; L2; L26; 650; SME business resilience; technology adoption; government support; financial resource; multigroup analysis